Study on the quantitative assessment of Staphylococcus aureus in the broiler chicken slaughtering line - Lin WANG; Ge ZHAO; Jianmei ZHAO; Yuehua LI; Tianfei HAN; Yubin GAO; Na LIU; Xiumei HUANG; Zhina QU; Juan WANG; Junhui LIU; Junwei WANG (Zhongguo shipin weisheng zazhi, 2020)
Objective To analyze the risk and key prevention and control points of Staphylococcus aureus in a large broiler slaughterhouse and to provide guidance for the scientific prevention and control of Staphylococcus aureus contamination in broiler slaughter. Methods Combining the monitoring data and investigation data of Staphylococcus aureus contamination in a large broiler chicken slaughterhouse, a quantitative assessment model was constructed using @ RISK 7 software, and a quantitative assessment was conducted on the four stages of chicken slaughter (depilation, cleaning chamber, pre-cooling and segmentation). Results Our research determined the predictive growth and decline pattern of Staphylococcus aureus in slaughtering process. It showed that the pre-cooling and segmentation and transmission links were the main risk contributor links of Staphylococcus aureus contamination. The critical risk control points of Staphylococcus aureus in broiler slaughtering were the concentration of Staphylococcus aureus in precooled pool water and hand-borne Staphylococcus aureus in workers with the correlation coefficient of 0.62 and 0.50, respectively. Conclusion The identification of key control points and precise control measures of Staphylococcus aureus in broiler slaughtering can effectively guarantee the health and safety of terminal chicken products.